2020
DOI: 10.21203/rs.2.22455/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defining Clusters of Young Autistic and Typically-Developing Children Based on Loudness-Dependent Auditory Electrophysiological Responses

Abstract: Background: Autistic individuals exhibit atypical patterns of sensory processing that are known to be related to quality of life, but which are also highly heterogeneous. Previous investigations of this heterogeneity have ordinarily used questionnaires and have rarely investigated sensory processing in Typical Development (TD) alongside Autism Spectrum Development (ASD). Methods: The present study used hierarchical clustering in a large sample to identify subgroups of young autistic and typically-developing ch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 82 publications
(118 reference statements)
0
7
0
Order By: Relevance
“…It is hoped that in the future the biomarker research in youth with neurodevelopmental disorders will benefit from larger samples, consistent methods, concerted efforts focusing on replication, building on recent consortia and other promising ongoing efforts 82,83 . This research should follow the lead of biomarker research in adults with severe mental disorders 84,85 and of other areas of medicine 86,87 , that can inform appropriate assessment techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hoped that in the future the biomarker research in youth with neurodevelopmental disorders will benefit from larger samples, consistent methods, concerted efforts focusing on replication, building on recent consortia and other promising ongoing efforts 82,83 . This research should follow the lead of biomarker research in adults with severe mental disorders 84,85 and of other areas of medicine 86,87 , that can inform appropriate assessment techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, previous studies indicate that neurophysiological pro files are highly heterogeneous in children with neurodevelop mental disorders, particularly with ADHD 77 and ASD 78 , meaning that the lack of replication on these measures may not be solely attributable to methodological limitations of original studies (e.g., unrepresentative and underpowered samples). This is demon strated by studies identifying datadriven subgroups of patients characterized by different EEG profiles, which appear associated with various clinical characteristics 79 and different rates of treat ment response 80,81 .…”
Section: Neurophysiological and Neuropsychological Biomarkersmentioning
confidence: 99%
“…Although the review did not formally metaanalyze group differences in Tb latencies, it also notes that prior studies examining Tb latencies reported substantial delays in the ASD group (45). Interestingly, prior research also suggests that there is considerable heterogeneity in auditory responses within both ASD and TD individuals (54)(55)(56). Furthermore, although the neurophysiological literature regarding somatosensory responses in ASD is not as well-developed as that investigating auditory responses, a few prior studies have documented that ERPs and ERFs to somatosensory stimuli in ASD might be delayed (57) or reduced in amplitude (58,59) relative to TD.…”
Section: Neurophysiological Event-related Responsesmentioning
confidence: 99%
“…Some prior studies have examined, in ASD, the convergence between questionnaire reports of sensory processing and ERP/ERF responses to auditory stimuli. For example, larger early neural responses to sounds could be related to reports of auditory distractibility or sensory sensitivity (55,67), and weaker later auditory responses might trend towards being associated with reports of hyporesponsiveness (68). Prior research has also explored associations between reported sensory behaviours and auditory mismatch/P3 responses (69,70) as well as ERP indices of auditory habituation (71).…”
Section: Neurophysiological Responses and Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation